Pengaruh Penyuluhan Menggunakan Media Video Terhadap Pengetahuan dan Sikap Tentang Anemia Pada Remaja Putri SMPN 1 Turikale Tahun 2020 - ASMAWATI, NUR; Icha Dian Nurcahyani; Kurnia Yusuf; Fitri Wahyuni; St Mashitah (UNIVERSITAS NGUDI WALUYO, 2021)
Anemia suppresses a condition where hemoglobin rates in the blood is lower than its normal value which is commonly caused by a lack of some gizi nutrients in foods that our body desperately needs. According to world Health Organization (WHO) data, anaemia in putri teenagers is still high enough, the world's anemic crossings range from 40-88%. The purpose of this scrutiny to verify whether there is a video media complimentary influence on the knowledge and attitude of anaemia in teenage daughter SMPN 1 Turikale. The type of scrutiny used is quasi Experimental ruin scrutiny using the normal reinsuance plan design also we mentioned with the term